Seamstresses Damn It! Struggle Trajectories and Self-Management in Argentina’s Popular Economies - Alioscia Castronovo (Íconos)
The purpose of this article is to contribute to the conceptualization of popular economies, creating a dialogue between authors and perspectives of the social sciences and drawing from an ethnographic research project in Buenos Aires. This article is about a journey of the social, productive, and political threads in time and space of the Juana Villca cooperative, which had as its protagonists’ migrant Bolivian workers. This cooperative introduces us to a heterogenous framework in popular economies. By reconstructing a genealogy of the processes that lead to the creation of a cooperative, there is a reflection on the struggles, potentials, and limits of self-management as a productive experimentation and articulation of a new communitarian-popular institutionalization.